Henoch-Schonlein Purpura in Children at Department of Pediatric, Bach Mai Hospital - Pham, Van Dem (H. : ĐHQGHN, 2020)
Henoch-Schonlein Purpura (HSP) is one of the most common vasculitis disease in children. The main symtomps are rash, arthritis, abdominal pain, and kidney disease. In particular, kidney involvement is important to predict long-term outcomes of disease. Aim: This study aimed to describe the epidemic characteristics, clinical manifestations and some laboratory findings of HSP in children. Subjects of study: We studied 50 patients diagnosed with HSP at Deparment of Pediatrics, Bach Mai hospital from 2017 to 2018. Results: The mean age was 9,1 ± 3,2 years, with the ratio of male to female to be 1,17:1. HSP has seasonal characteristics, it was more common in the spring (43.4%) and the winter (26.1%). 44% of HSP cases were preceded by an acute infectious or allergic illness. The common clinical manifestation was reddish-purple spots such as the sock (90%) and digestive tract symptoms (68%), nephritis (18%). At the end of research, 78% of cases was complete remission, 16% of cases relapse and 6% non response. Conclusion: The common clinical manifestation was reddish-purple spots such as the sock and digestive tract symptoms. Out come of HSP was high complete remission rate.